The Value of Banks and Their Business Models to Society - Harald Benink; Ata Can Bertay; Michiel Bijlsma; Teunis Brosens; Andreas Bley; Allard Bruinshoofd; Jakob de Haan; Asli Demirgüç-Kunt; Lex Hoogduin; Aerdt Houben; Harry Huizinga; Wilfred Nagel; et al. (SUERF - The European Money and Finance Forum, 2014)
Banks play a central role in the functioning of the economy. Not only do they allocate financial resources, they also collectively create money in the process of granting loans. In this way, they have a considerable impact on the type of activities that are financed in society. During the financial crisis, it became clear that the banking sector at large was not sufficiently stable and customer-focused. Since then, banks and regulators alike have been busy reviewing bank business models, and several committees have been installed to investigate the desired scale and scope of banking activities.
Keywords: G21; G34; G38; 330; Bank business models; Too-big-to-fail; Big banks; Großbank; Bankenkrise; Geschäftsmodell; Bankenregulierung